IN VITRO BIOMASS PRODUCTION OF LIVER-PROTECTIVE COMPOUNDS FROMGLOBE ARTICHOKE (CYNARA SCOLYMUS L.) AND MILK THISTLE (SILYBUMMARIANUM) PLANTS - BekheeT, S A (Emirates Journal of Food and Agriculture, 2011)
The evolving importance of the plant secondary metabolites has in recent years resulted in a great interest of natural medicinal compounds, particularly their production by means of plant cell culture technology. The main advantage of this technology is that it provides continuous, reliable source of plant pharmaceuticals that could be beneficial in large-scale production. Globe artichoke and Milk thistle plants are considered important medicinal herbs producing active ingredients that treat liver diseases. Globe artichoke extract is recommended for liver damage disease and poor liver function. Cynarin, the main active compounds of artichoke has several pharmaceutical actions such as liver protection and re-growth of liver cells. Otherwise, silymarin extracted from Milk thistle has been used to treat hepatitis and liver damage. This work discusses different approaches of biotechnology used for biomass production of Globe artichoke and Milk thistle as sources of their active ingredients. Optimization of different physical conditions such as temperature, aeration, agitation light and chemical factors like addition of growth regulators and precursors to culture media for in vitro production of these active compounds have been described. Moreover, transformed hairy roots cultures, caused by infection of Agrobacterium rhizogenes has been discussed as an important technique for in vitro maximization of such secondary metabolites production.